Education in Speech Therapy – history, present, future. Celebrating ten years of Speech Therapy at the University of Warmia and Mazury in Olsztyn - Osowicka-Kondratowicz, Magdalena (Papers in Linguistics, 2024)
The article is devoted to presenting the speech therapy major at the University of Warmia and Mazury in Olsztyn after ten years of its functioning. The task is to record the history of the major, present the teaching and research areas undertaken in the field as well as analysing selected aspects of speech therapists’ education and indicating developmental perspectives for the major.